Mechanism of eliminating UDP redundancy control packets in OpenFlow network - Hui HU; Ming CHEN; Bo LIU; Bo XU; Chang-you XING; Chao HU (Tongxin xuebao)
Large numbers of redundant control packets produced by connectionless UDP flows may engender serious influence over the performance of the SDN controllers and networks.The endangerment of the redundant control packets for the performance of SDN controllers by testing and modeling was firstly analyzed,and then a basic solution to solve the problem was formed.Therefore,a preinstalling flow-tables ＆amp; filtering redundant packets (PFFR) mechanism was proposed.By preinstalling flow tables,PFFR limited the initial rate of control packets in UDP flows,and through installing flow tables according to paths and utilizing the redundant packets filtering algorithm,PFFR eliminated redundant packets rapidly.A prototype system based on PFFR was implemented and tested.The experimental results prove that the PFFR mechanism can effectively improve the performance of the controller.